2021
DOI: 10.3390/smartcities4020036
|View full text |Cite
|
Sign up to set email alerts
|

Rider Perceptions of an On-Demand Microtransit Service in Salt Lake County, Utah

Abstract: On-demand microtransit services are frequently seen as an important tool in supporting first and last mile operations surrounding fixed route high frequency transit facilities, but questions remain surrounding who will use these novel services and for what purposes. In November 2019, the Utah Transit Authority launched an on-demand microtransit service in south Salt Lake County in partnership with a private mobility operator. This paper reports the results of an expressed preferences survey of 130 transit ride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Our review of the feasibility and performance assessment studies revealed that these studies utilize different methods to define microtransit service zones and that there is no known systematic method for identifying service zones in the literature to the best of our knowledge. A TCRP Synthesis of Transit Practice report ( 7 ) and a more recent study by Macfarlane and Atchley ( 8 ) also highlighted this research gap.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our review of the feasibility and performance assessment studies revealed that these studies utilize different methods to define microtransit service zones and that there is no known systematic method for identifying service zones in the literature to the best of our knowledge. A TCRP Synthesis of Transit Practice report ( 7 ) and a more recent study by Macfarlane and Atchley ( 8 ) also highlighted this research gap.…”
Section: Methodsmentioning
confidence: 99%
“…Many of the feasibility studies we reviewed considered the service areas as given (typically determined by the agency, and starting as pilot programs) and conducted feasibility analysis on these areas using one or a combination of approaches. Examples are: Via Mobility, LLC ( 5 ), Macfarlane and Atchley ( 8 ), Kang and Hamidi ( 9 ), Via, VTrans ( 10 ), Mountain Line ( 11 ), and SRF Consulting Group ( 12 ). Many of these studies used various geographic information system (GIS) techniques for visualizing/mapping to provide spatial context to the analysis as well.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vehicle related cos ts = (Vehicle Purchased× (1 + Tax)× Price) + Cars × (Insurance + Maintenance + Registration) (9) In this case, it is assumed that the microtransit program purchases one vehicle per driver hired, unless there are spare vehicles available. Spare vehicles become available once a driver leaves the program.…”
Section: Cost Module Sfdmentioning
confidence: 99%
“…Recognizing the pivotal role of transportation as a social determinant of health, several innovative solutions have been employed to effectively address these challenges. One such solution is the implementation of microtransit programs, which have shown promise in mitigating barriers related to SDOH [8][9][10]. As defined by the Federal Transit Administration, Microtransit is a technology-enabled, multi-passenger transportation service that operates on dynamically generated routes [11].…”
Section: Introductionmentioning
confidence: 99%